TRANSPORTATION COMMUNICATIONS AND GEOPOLITICS IN THE GREAT SILK ROAD REGION - MIRZAEV, Rustam (CENTRAL ASIA AND THE CAUCASUS, 2005)
One hundred years ago when scholars were just beginning to coin the term “geopolitics,” states relied on force to protect their interests. No matter how skillful the diplomats were, the army remained the only guarantor of all treaties and agreements. A new force destined to change the world—transnational corporations—came to the fore in the latter half of the 20th century and gradually developed into a new political factor. These giants were born in the developed and rich countries, which, however, were not very strong militarily. Indeed, some of them represented Japanese and German capital (the mil itary budgets of these countries could hardly be compared with America’s military spending). Without a single shot the transnational corporations, as welcome guests in nearly all Third World countries, accom plished what in the past could be secured solely by the use of arms: economic and political domination. It was the transnational corporations that gave birth to the globalization ideas; it is the transnational cor porations that are translating them into life as being best suited to their interests. The world economic space is becoming a reality at a fast pace, with the European Union setting an example. It took it over 50 years to move away from local agreements, under which neighbors acquired the status of most favored nations (the European Coal and Steel Community, etc.), to common governing bodies (the European parliament and its institutions). United Europe with its single currency and trans parent internal boundaries is the ideal, which the larger part of mankind is aspiring to achieve and which it will achieve by all means. The national interest idea is the key concept of geopolitics, geographic location being one of its basic factors. Indeed, the place where the nation takes shape is the most stable parameter of its existence. What is a strategic forecast of the world’s geopolitical makeup for the 21st century? What place can Central Asia and its closest neighbors hope to acquire? The answers are not merely interesting, they are vitally important for all of us living in Central Asia. Political scientists and futurologists predict clashes of civilizations in the 21st century. Nikolai Danilevskiy, Russian publicist writer and sociologist, was the first to tie together historical progress and civilizations in his famous book Rossiai Evropa (Russia and Europe) first published in 1868. 1 He described cultural-religious communities, or cultural-historical types, rather than states and nations as the main actors on the historical scene. (Later political scientists agreed to call them “civilizations.”) Still later the theory was further developed by German philosopher Oswald Spengler, Russian philosopher Konstantin Leontiev, and prominent Eurasians Petr Savitskiy and Lev Gumilev. British historian Arnold Toynbee in his definitive multi-volume work A Study of History 2 offered even more profound treatment of the same subject. He classified civilizations and formulated a theory of their development, which he called Challenges and Responses. Today, the science of geopolitics is being developed by Harvard professor Samuel Huntington, who in 1993 published his definitive work The Clash of Civilizations, in which he convincingly demonstrated that economics and ideology would no longer provoke conflicts in the 21st century. This role, he argued, would belong to the differences between civilizations which would thus emerge as the dominant factors of world politics.